ELDERLY HEALTH AND ITS CORRELATIONS AMONG UZBEK POPULATION - PULATOVA, GOOLBAHOR (Nagoya J Med Sci, 2012)
This study was conducted from November, 2007 to May, 2008 to evaluate the health status of the elderly and correlated factors affecting their health. We collected data from 682 individuals 65 years or older (214 male) from greater Tashkent City in Uzbekistan. The study revealed that 75.4% of the respondents were aged <75 years and that 16.8% of them were not educated. About three-quarters of the respondents rated themselves as ‘healthy.’ The odds ratios (ORs) and 95% confidence intervals (CIs) were estimated through a logistic regression model to determine correlations of elderly health, and adjusted for age and sex. The elderly who had additional income were 2.6 times (95% CI=1.8–4.0) more likely to be healthy. Similarly, those <75 years old (OR=1.5, 95% CI=1.0–2.2), were able to do everyday duties (OR=6.0, 95% CI=3.8–9.3), and those who were married (OR=4.1, 95% CI=1.7–9.7) were also healthy. Conversely, males (OR=0.6, 95% CI=0.4–0.9) and the elderly who were supported by sources other than their own income from work were not healthy. We concluded that having a strong family relationship and adhering to a traditional lifestyle are important for protecting elderly health in Uzbekistan. Substantial financial support and personal care are necessary for the elderly. Creating a healthy atmosphere for them at an individual and family level could ensure a better quality life for the elderly in Uzbekistan.